2020
DOI: 10.3390/v13010044
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-α2b Treatment for COVID-19 Is Associated with Improvements in Lung Abnormalities

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causes coronavirus disease 2019 (COVID-19), a lung disease that may progress to systemic organ involvement and in some cases, death. The identification of the earliest predictors of progressive lung disease would allow for therapeutic intervention in those cases. In an earlier clinical study, individuals with moderate COVID-19 were treated with either arbidol (ARB) or inhaled interferon (IFN)-α2b +/−ARB. IFN treatment resulted in accelerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…However, it has been reported that inborn errors of type I IFN immunity are associated with severe COVID-19 [ 96 ] since the low type I IFN activity triggers IL6 and NF-α mediated pro-inflammatory responses and cytokine storm [ 97 ]. Recent reports suggest that IFN-α therapy could be a potential management strategy for COVID-19 [ 98 , 99 ]. Therefore, IFN-α treatment for COVID-19 patients with CKDs needs further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that inborn errors of type I IFN immunity are associated with severe COVID-19 [ 96 ] since the low type I IFN activity triggers IL6 and NF-α mediated pro-inflammatory responses and cytokine storm [ 97 ]. Recent reports suggest that IFN-α therapy could be a potential management strategy for COVID-19 [ 98 , 99 ]. Therefore, IFN-α treatment for COVID-19 patients with CKDs needs further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for reduced interferon responses in our present study, where all hamsters were adult male animals, awaits further investigation. Moreover, taken together, the immune profile we have identified together with the respiratory tract pathology suggests hamsters to be an ideal model to explore these mechanisms and test therapeutics such as type I interferons 54,55,76 or interferon lambda 77,78 , both of which have demonstrated effectiveness in treating COVID-19 patients [79][80][81] but more research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Lung infection in COVID-19 may evolve into systemic involvement. Also, IFNs specially IFN-α2b are capable of preventing lung abnormalities in such patients ( Zhou et al, 2021 ). All of these statements emphasize the role of IFN therapy in severe acute CoVs disease.…”
Section: Introductionmentioning
confidence: 99%